Pelaksanaan Pengambilan Sidik Jari dalam mengungkap Pelaku Tindak Pidana Pencurian - I Kadek Aris Setiawan; l Nyoman Gede Sugiarta; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
The increase in the crime of theft has become one of the concerns in the community, so in this case the implementation of fingerprinting in exposing the crime of theft is to reveal the identity of the victim of theft. Based on these problems, the purpose of this research is to analyze the role of fingerprints in uncovering the criminal act of theft and the process of taking fingerprints in proving the perpetrator of the crime of theft. The research method used is normative and empirical legal method. Sources of data used are primary and secondary sources of law. Data collection techniques by interviewing, taking notes, quoting, reading, and summarizing the literature. After the data is collected, it is analyzed qualitatively. The result shows that the role of fingerprints in uncovering criminal acts of theft is that they can be used as evidence, by using a system or method of fingerprint identification, fingerprint records in the form of letters or expert statements can be used as additional evidence in addition to other evidence. found at the scene of the case in conducting an investigation.